Effects of cessation of terbutaline treatment on airway obstruction and responsiveness in patients with chronic obstructive pulmonary disease. - de Jong, J. W. (1996)
BACKGROUND: Cessation of regular therapy with inhaled beta 2 agonists in patients with asthma may lead to a temporary deterioration of lung function and airway responsiveness. Few such studies have been reported in patients with chronic obstructive pulmonary disease (COPD), so an investigation was carried out to determine whether rebound airway responsiveness and rebound bronchoconstriction also occurs in COPD and if there is any relationship with the dose of beta 2 agonist being used. METHODS: Lung function (forced expiratory volume in one second (FEV1) and peak expiratory flow (PEF)), airway responsiveness (PC20 methacholine (PC20)) and symptoms were assessed in a double blind, placebo controlled crossover study during and after cessation of two weeks regular treatment with placebo, and low dose (250 micrograms) and high dose (1000 micrograms) inhaled terbutaline via a dry powder inhaler (Turbohaler) all given three times a day. Sixteen non-allergic patients with COPD of mean (SD) age 58.7 (6.5) years, FEV1 57.1 (12.8)% of predicted, and reversibility on 1000 micrograms terbutaline of 4.5 (3.5)% predicted were studied. PC20 and FEV1 were measured 10, 14, 34 and 82 hours after the last inhalation of terbutaline or placebo. Measurements performed at 10, 14, and 34 hours were expressed relative to 82 hour values in each period, transformed into an area under the curve (AUC) value and analysed by ANOVA. RESULTS: Mean morning and evening PEF increased during terbutaline treatment. PC20 and FEV1 did not change after cessation of terbutaline treatment. CONCLUSIONS: Cessation of regular treatment with both low and high dose inhaled terbutaline does not result in a rebound bronchoconstriction and rebound airway responsiveness in patients with COPD.